2005
DOI: 10.1021/ic0515103
|View full text |Cite
|
Sign up to set email alerts
|

E2(CN)2 (E = S, Se) and Related Compounds

Abstract: A synthetic, spectroscopic, and theoretical study of Ex(CN)2 (E = S, Se; x = 1-3) is described. The X-ray structures of Se2(CN)2 and Se3(CN)2 have been determined. Se2(CN)2 crystallizes in a chiral space group with the CN groups approximately gauche.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
22
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 19 publications
6
22
0
4
Order By: Relevance
“…The calculated electrostatic surface potential ( Figure 2) clearly shows the four σholes one can anticipate, two in the prolongation of the Se−Se bond, and two in the prolongation of the C−Se bonds. 20 Its crystal structure (Figure 3, XUNHOF) 21 shows indeed that they are interacting all four with the nitrogen lone pair of neighboring molecules. As shown in Table 1, the interactions are short and highly directional.…”
Section: Intermolecular Chb Interactions In Diselenidesmentioning
confidence: 96%
“…The calculated electrostatic surface potential ( Figure 2) clearly shows the four σholes one can anticipate, two in the prolongation of the Se−Se bond, and two in the prolongation of the C−Se bonds. 20 Its crystal structure (Figure 3, XUNHOF) 21 shows indeed that they are interacting all four with the nitrogen lone pair of neighboring molecules. As shown in Table 1, the interactions are short and highly directional.…”
Section: Intermolecular Chb Interactions In Diselenidesmentioning
confidence: 96%
“…The agreement is acceptable except for a considerable discrepancy in the wavenumber of the m 3 mode. In this light it is worth keeping in mind that S(CN) 2 is a rather unstable molecule making the study of its infrared spectrum particularly challenging, which may be the reason why the results of four such studies [4,[10][11][12] are in some disagreement. The plethora of low frequency normal modes will have significant consequences for the appearance of the rotational spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…In the same work it was reported that polyselenocyanogen could alternatively be prepared from selenocyanogen by heating in high boiling solvents such as xylenes and decalin. We have examined a number of selenium-containing systems [39][40][41][42][43][44] and it is reasonable to anticipate that CSe-N analogues of the C-S-N described here could exist and thus we conducted some preliminary experiments on (SeCN) x and it is appropriate to include our preliminary observations here.…”
mentioning
confidence: 99%